2003
DOI: 10.1007/s00221-003-1643-x
|View full text |Cite
|
Sign up to set email alerts
|

Human adaptation to rotated vision: interplay of a continuous and a discrete process

Abstract: The mechanisms for adaptation to visual rotation were investigated by exposing subjects to different rotation angles in a stepwise fashion. We found that response direction continuously changed to compensate for the imposed rotation, but this change was limited to 90 deg. Larger changes were accomplished by inverting both spatial axes (which is equivalent to a 180 deg rotation), and then gradually changing response direction "backwards" to the prescribed value. The angle of 0 deg had no such limiting value lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 12 publications
4
41
1
Order By: Relevance
“…In accordance with previous work (Bock et al, 2003Roby-Brami & Burnod, 1995), subjects adapted gradually in both paradigms. However, responses were consistently more efficient throughout the adaptation phase with rotated feedback.…”
Section: Hand Adaptationsupporting
confidence: 87%
See 1 more Smart Citation
“…In accordance with previous work (Bock et al, 2003Roby-Brami & Burnod, 1995), subjects adapted gradually in both paradigms. However, responses were consistently more efficient throughout the adaptation phase with rotated feedback.…”
Section: Hand Adaptationsupporting
confidence: 87%
“…The hypothesized existence of a common mechanism seems to be at odds with the finding that adaptation to double-step targets doesn't exceed 15°even if step magnitude is much larger , while adaptation to visual rotation shows no such constraint (Cunningham, 1989;Bock et al, 2003). This discrepancy between paradigms cannot be explained by strategies, since it persists during the aftereffect phase.…”
Section: Hand Adaptationcontrasting
confidence: 47%
“…Indeed, a recent review states the following: "so far, there is no convincing evidence that skill acquired in kinematic adaptation tasks needs to undergo stabilization" (Robertson et al, 2004). Instead, it has been suggested that changes in the time course of adaptation with successive visuomotor rotations simply reflect repeated recalibrations of a single learned reference system (Bock et al, 2003). In this framework, the recalibration process depends on the carryover of aftereffects across conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This means that there is a novel relation of ones' own movements to their visually perceived consequences such as the location of the impact of the head of the hammer or the position of the cursor on the computer monitor. During recent years evidence has been accumulated which points to the existence of rapid discrete and slower continuous processes of adaptation (e.g., Abeele & Bock, 2001;Bock, Abeele, & Eversheim, 2003;Sülzenbrück & Heuer, 2009aWerner & Bock, 2010), which are perhaps related to discrete and continuous processes of motor planning (Ghez et al, 1997). Typically discrete processes approximate the visuo-motor transformation, and continuous processes incrementally increase the accuracy of the initial approximation.…”
Section: Introductionmentioning
confidence: 99%